Estimating the Need for Additional Places in the General Education System of Russia in 2014–2025 - Vyacheslav Bashev; Dmitry Dekhant; Vyacheslav Lozing (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
This paper analyzes the growing shortage of places in the general education system of Russia in 2014–2025. We identify the following key factors: a) the need to provide places for children who are now enrolled in afternoon or evening sessions; b) expected growth in the number of school students to be caused by anticipated demographic changes; c) increase in the number of places in general education institutions by 2020 scheduled by national and local programs; d) possible loss of the buildings that were 50–70% or >70% worn as of 2014. As seen from the calculations based on the available Federal State Statistics Service data, regulatory instruments and excerpts provided by Russian governmental authorities, the expected need for additional places in general education institutions may be as high as 4.67 mln places. We demonstrate how the growing number of school-age children, the new requirements to school organization and learning conditions and the physical wear of school facilities increase the need for additional places. We have established that the scheduled measures to provide more education places do not cover the expected shor tage of places in the general education system of Russia.